Comparison the Efficacy of Meloxicam and Ketoprofen in Alleviating Pain Following Ovariectomy in Rats - Azin Tavakoli; Ali Akbar Shabannia; Leila Mohammadyar (Iranian Journal of Veterinary Surgery, 2012)
Objective: The purpose of this study was to compare the efficacy of two NSAIDs, meloxicam and ketoprofen in controlling post-operative pain following ovariectomy in rats. Study design: Experimental study Animals: Twenty one healthy and adult female Sprague-Dawley rats weighting approximately 200 gr. Methods: Intramuscular injection of the combination of xylazine (10 mg/kg) and ketamine (75 mg/kg) was used to induce general anesthesia in all rats. Then the selected rat was assigned for a group prior to surgery in the following order: Group A, received no extra analgesic, group B, received subcutaneous injection of 5 mg/kg ketoprofen at the time of induction of anesthesia and group C received subcutaneous injection of 2 mg/kg meloxicam (7.5 mg/ml) at the time of induction of anesthesia. Then ovariectomy was performed through two dorso-lateral abdominal incisions.  Score of pain at 2, 4 and 24 hours after the surgery using VAS, serum levels of cortisol and CPK at 2 hours after the surgery were evaluated in all rats. Results: The score of pain was significantly different in group A, compared to group B and C (P=0). Also the concentration of cortisol was significantly increased in all groups following the surgery. This increase was significant in group A compared to group B and C (P<0.05). Although CPK concentration was increased significantly in all groups after the surgery, no significant correlation was found among groups. Conclusion: It is concluded that either meloxicam or ketoprofen have similar effects in controlling pain following ovariectomy in rats.